Determinasi Faktor-Faktor Keamanan E-Banking Terhadap Kepercayaan dengan Pendekatan Technology Acceptance Model - Qamaruzzaman, M. Haris; Surarso, Bayu; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Safety  and  convenience  factor  is  important  for  confidence  in  the  use  of  e-banking.  This  study  aimed  to  investigate  the  factors determination  using  e-banking  approach  to  technology  acceptance  model,  and  analyze  the  determination  of  the  factors  the  use  of  ebanking  with  the  Technology  Acceptance  Model  approach.  Technology  Acceptance  Model  (TAM)  is  a  model  used  to  explain  the acceptance of the technology to be used by users of the technology. In the context of this study, TAM raises the safety factor and the factor of ease of use of e-banking to e-banking trust uses. This research is a field research (field research) with a quantitative approach that examines the issues being studied. Sampling method using random sampling technique as much as 100 respondents. Data collection techniques are the primary data by distributing questionnaires to the users e-banking. While the secondary data that other reports related to research. The data analysis techniques used include descriptive statistics and analysis phases of statistical regression analysis. These results prove that the safety factor has a significant and positive effect on user confidence in e-banking proven Ho is rejected and Ha accepted  with  a  significance  level  of  0.001  (<0.05),  while  the  convenience  factor  also  has  a  positive  and  significant  impact  on  user confidence in e-banking proven Ho is rejected and Ha accepted with a significance level of 0.000 (<0.05).Keywords: Factor Security; Ease; Confidence Use of e-banking; Technology Acceptance Model (TAM)